DESCRIPTION OF ALTERNATIVE MEDICINE HISTORY IN BREAST CANCER AND COLORECTAL CANCER PATIENT IN HOSPITALS IN DENPASAR - Suari Utami, Ni Made; Affandi, Yudo; Wara Samsarga, Gede; Satya Nugraha, I Made Sindhu; Wibawa Manuaba, I. B. Tjakra (Bali Journal of Medical and Health Sciences, 2013)
Reluctance to get treatment is one of the reasons why cancer patients come at the advance stage to health care provider. Numerous information of alternative medicine seems to influence the patients to try alternative medicine and delay their treatment in hospital. A descriptive study is conducted in 2 hospitals in Denpasar to obtain the description of alternative medicine history in cancer patients, with breast cancer and colorectal cancer patients as samples. Total samples were 38 patients, with 23 of them ( 60.5% ) have tried the alternative medicine, whereas 13 patients (56.52%) after visiting the health care provider. Among those who tried the alternative medicine, 14 patients (60.87%) seek this medicine because of their fear to the conventional medicine. The most popular method of alternative medicines is herbal medicine. Most of the patients got information about alternative medicines from people whom close to them such as their family, relatives, and neighbors. However, most of these patients, who have tried the alternative medicine, in the end came back to the health care provider/ hospital after they realized that the result of the alternative treatment did not improve their health condition. Keywords: alternative medicine, breast, colorectal, cancer Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}